L’intesa demo-fobica all’origine del movimento neoliberale. Nascita di un concetto polemico nell’Europa fra le due guerre mondiali - Giachetti, Fulvia (Studi Politici, 2022)
The article investigates the genealogy of the neoliberal movement in Europe between the two World Wars, reconstructing the semantic politics of the different currents that converged and articulated in it in 1938 at the Lippmann Colloquium, focusing on the common aversion to political democracy, understood both as a form of government and in a broader sense as a process of politicizing societies. This ‘demo-phobic’ element constitutes one of the main factors of understanding between Austrian marginalism and German ordoliberalism, two strongly distant traditions of thought, especially about the quality of state interventionism in the economic field: for the former minimal-adaptive, for the latter constructivist-decisional. An example of this understanding is reflected in globalist thinking and formalised at the Colloquium. In addition to constructing a historical-conceptual itinerary on the origins of neoliberalism, the article aims, from its introduction, to critically reflect on the polemical uses and meanings of the category, which differ according to the time periods considered, to clarify some lines of the recent debate within political studies on this category that is as decisive as it is contested in the contemporary political lexicon.